2010
DOI: 10.1002/ppap.200900114
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine Plasma Treatments of Poly(propylene) Films, 2 – Modeling Reaction Mechanisms and Scaling

Abstract: IntroductionThe fluorination of the surface layers of hydrocarbon polymers modifies the wetting properties of the polymer by decreasing the surface energy and increasing hydrophobicity. [1][2][3] The fluorination process usually entails the removal of hydrogen from the hydrocarbon polymer backbone, forming an alkyl site, and the passivation of the alkyl site with a fluorine atom. [4] As most hydrocarbon polymers are heat sensitive, it is desirable for the fluorination to take place at low temperatures. As such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…In Part 2 of this paper,11 we report the results from an integrated plasma and surface kinetics model that was developed simultaneous with the reported experimental work to describe the reactions in the F 2 /Ar plasma treatment of a PP film surface.…”
Section: Introductionmentioning
confidence: 99%
“…In Part 2 of this paper,11 we report the results from an integrated plasma and surface kinetics model that was developed simultaneous with the reported experimental work to describe the reactions in the F 2 /Ar plasma treatment of a PP film surface.…”
Section: Introductionmentioning
confidence: 99%
“…Cold plasmas modification of polymers can change their physical and chemical surface characteristics . For example, Yang et al showed that affixing fluorine to a hydrocarbon surface can increase its hydrophobicity. Savoji et al observed changes in surface composition and drastic improvement in wettability.…”
Section: Plasma‐based Surface Treatmentmentioning
confidence: 99%
“…The model was developed by Kushner and his team. [23][24][25] It is composed of several modules and can be used to investigate the electron behavior (like non-local 26 and harmonic effects 27 ), the chemical characteristics (like the chemical composition 28 ) and the surface kinetics (like etching, deposition, and implantation 29 ). In this work, the three main modules are applied, i.e., the Fluid Kinetics Module (FKM), the Electron Energy Transport Module (EETM), and the Electromagnetic Module (EMM).…”
Section: Model Descriptionmentioning
confidence: 99%